Death of a neighborhood Scrooge - Levine, Laura, 1943- (Levine, Laura, 1943- Jaine Austen mystery., 2018)
Scotty Parker is a former child star who once played Tiny Tim, but now he<U+2019>s grown up into the role of neighborhood Scrooge. He cuts the wires on his neighbors<U+2019> Christmas lights and tells local kids that Santa had a stroke. And his miserly, bah-humbug attitude lasts year-round<U+2014>a fact known all too well by his current wife, his ex-wife, his maid, and many more. Scotty thinks he can stage a comeback with the screenplay he<U+2019>s working on (The Return of Tiny Tim: Vengeance Is Mine!), and Jaine<U+2019>s been reluctantly helping him edit it. So when Scotty is bludgeoned with a frozen chocolate yule log and the police start making a list of suspects and checking it twice, Jaine<U+2019>s name is unfortunately included. True, she<U+2019>s been under some stress, with Lance trying to set her up on dates and her fickle feline taking a sudden liking to someone else<U+2014>but she<U+2019>s not guilty of murder. Now she just has to prove it, by using her gift for detection and figuring out who committed this holiday homicide.